Cartometrics and genetic-morphological characteris- tics of the soil cover by means of GIS-technologies - Klebanovich, Nikolai V.; Prokopovich, Sergey N.; Sazonov, Aliaksei A.; Kulikova, Hanna S. (Journal of the Belarusian State University. Geography and Geology, 2017)
The article presents a study cartometric and genetic-morphometric characteristics of the soil cover three administrative regions of Belarus Kletsk, Puhovichi and Cherven, a scale number 1 : 10 000, 1 : 50 000, 1 : 200 000. The application of technology to the GIS analysis allowed us to analyze not only the classification belonging to the soil contours but also their geometry and morphometry, which gives grounds to speak about a qualitatively new level of analysis – genetic and geometric. Treatment of a number of large-scale soil maps and identifying the main genetic and geometric characteristics – the size, shape and degree of irregularity of the boundaries of the elementary soil areas, allowed us to obtain a significant amount of inventory and cartometrics data, subsequent evaluation of which showed a high authorial subjectivity in the preparation of soil maps of small and medium scale, in particular, unjustified overstatement of the share and average area of sod-podzolic soils due to massive absorption of neighboring contours, mainly palpitating. The results of a study aimed at assessing the accuracy and reliability of the analogue soil maps in comparison with the digital representation of the soil for the development of more accurate and objective algorithms compile and analyze the latter.
Keywords: digital soil mapping; elementary soil areas; land information systems; geodatabases; GIS analysis